Proper Management of Underweight and Anemia in Tuberculosis Patients Increases The Improvement Time During Two-Week Treatment Follow-Up - Saputra, Tetra Arya; Wibowo, Adityo (Medula, 2024)
Tuberculosis (TB) continues to be the leading cause of disease and mortality caused by chronic pulmonary infection. The World Health Organization (WHO) considers that one-third of the global population is infected with Mycobacterium tuberculosis (Mtb).  Mycobacterium tuberculosis infection results in persistent lung damage, which is characterized by ongoing inflammation that damages lung tissue. The patient additionally experienced a cough for almost one month, with clear mucous, absence of blood, and mild shortness of breath. Patients had decreases in body weight and loss of appetite for about three weeks. Night sweats appeared within one month. There was no specific complaint of gastrointestinal symptoms. The patient's nutritional management was focused primarily on oral intake, with a total daily consumption of 1690 kcal. The daily protein, carbohydrate, and fat consumption is divided into 42.45 grams of protein, 253.5 grams of carbohydrates, and 37.5 grams of fat. There was no history of food allergy from the patient, therefore we decided not to impose any dietary restrictions. The improvement in body weight was used to monitor the outcome of the nutritional intervention. Nutritional issues have emerged as a significant contributor to an increasing percentage of individuals with low hemoglobin (Hb), influencing TB-related morbidity. The most prevalent causes of anemia in tuberculosis are nutritional deficiencies and malabsorption as a result of appetite loss. Poor intake of food has also been linked to an increased risk of disseminated TB. To improve treatment outcomes, nutritional support should be provided in addition to tuberculosis medicine.